Correlations between compressive strength and tensile strength of concrete for two-layers pavement with exposed aggregate - Konopska-Piechurska, Małgorzata; Jackiewicz-Rek, Wioletta; Łukowski, Paweł (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In the paper the results of experiments on concrete pavement with exposed aggregate technology placed in two technological layers were presented. The following properties were measured: compressive strength, flexural strength by two methods: two-point loading and centre-point loading, tensile splitting strength of cubic and cylindrical samples. The study was performed for two type of concrete with a maximum aggregate size Dmax 8 mm (concrete applied to the upper layer of concrete pavement - GWB) and Dmax 22 mm (concrete used for the bottom layer - DWB). After the analysis of the tests, the correlations between compressive strength and tensile strength, measured by flexural strength and tensile splitting strength, were determined for the used two-layers concrete pavement with exposed aggregate depending on applied Dmax.